ANALISIS KEMAMPUAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL MOMENTUM DAN IMPULS - Sisi Pravidya; Judyanto Sirait; Erwina Oktavianty (Universitas Tanjungpura, 2022)
This research aims to describe the problem solving ability of students in solving momentum and impulse essay questions at SMA Taruna Bumi Khatulistiwa. This research used qualitative research with a descriptive method. The sample in this research was 20 students consisting of 10 male students and 10 female students. The problem-solving stages in this research used the problem-solving ability that have been introduced by Heller, Keith, and Anderson. Based on data analyzed, it can be seen that the students' abilities at the stages of visualizing the problem, physics description, plan a solution, executing the plan, and check and evaluate are 69%, 57%, 73%, 58 %, and 30%. Each stage of problem solving is in the good, enough, good, enough, and less categories. Base on gender, female students achieved higher score than male students in solving the problems.